Implementation and application of a distributed hydrological model using a component-based approach. (June 2016) - Long, Yinping; Zhang, Yaonan; Yang, Dawen; Luo, Lihui
Abstract: The application of a model to different study areas often requires that the model be modified to conform to specific characteristics, but this can be challenging due to the poor readability and reusability of the legacy codes. Component-based programming supported by a modelling framework provides a generic means to develop and modify models. This paper describes the development of a distributed hydrological model using a component-based modelling framework, which is implemented as a set of functional components that are integrated at runtime. The model was applied to runoff simulation in a large scale and data scarce alpine basin, and was further improved by incorporating a simple empirical soil freezing-thawing component. The results show that the componentised model reproduced the daily and monthly flow hydrograph with 'good' accuracy. The framework is shown to be flexible enough for model development and model modification. Highlights: A new component-based framework is introduced. A distributed hydrologic model was implemented based on this framework. The model is applicable in large scale and data scarce alpine basins. A simple empirical soil freezing-thawing component was incorporated. Remote sensing data based parameterisation scheme was adopted.